Penerapan Teknologi Pengolahan Singkong Menjadi Tepung Mocaf Sebagai Upaya Mendukung Desa Mandiri Mocaf Desa Pesangkalan Kabupaten Banjarnegara - Sarno; Eko Apriliyanto; Dwi Ari Cahyani (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2022)
The Karunia Village of Pesangkalan Banjarnegara group is an industrial partner that has great cassava potential to be developed into mocaf flour. Limitations of technology, knowledge and skills are one of the problems faced. The aim of the activity is to help improve the welfare of cassava farmers through the application of appropriate technology, increase knowledge and skills about processing mocaf flour and its derivatives and strengthen startup development cooperation with competitiveness. The methods used are community education, training, and mentoring. The results of the activities are as follows; (a) application of appropriate technology in the form of Food Grade Dehydration machines, sieving machines, chopper machines, kneading machines and steam mocaf noodle machines, (b) flour products and mocaf noodles, (c) packaging innovations for mocaf noodle products, (d) standard documents mocaf processing operational procedures. The conclusion of the activity had an impact on increasing the knowledge and skills of cassava farmers by 85% from the previous condition, increasing the selling value of mocaf noodle products, and strengthening university cooperation with industrial partners.